Efficacy of Enterosorbent Based on Pectin, Inulin and Fennel Extract in Treating Children with Atopic Dermatitis: «Case-Control» Prospective Study - Elena I. Danilova; Oksana Yu. Trusova; Anton N. Roschupkin; Zinaida A. Veterkova; Ekaterina I. Golovacheva; Tatiana N. Ignatova ("Paediatrician" Publishers LLC, 2016)
Background: Atopic dermatitis (AD) is an important issue, significance of which is determined by the incidence increase, chronic, relapsing course of the disease, and poor treatment efficacy.Objective: Our aim was to study clinical efficacy of enterosorbent based on pectin, inulin and fennel extract in combined AD treatment in children.Methods: «Case-control» prospective study included children from 3 to 11 years admitted to hospital with moderate AD.Results: 20 patients included in the study took enterosorbent in addition to the basic therapy, 20 patients had only basic therapy. Compared groups were matched by sex, age, and AD severity by SCORAD scale. Cutaneous AD manifestations in the main group were arrested average over the period of 3.4 ± 1.2 days, in the control group - of 4.7 ± 1.5 days (p < 0.001), skin itch - of 4.0 ± 0.9 and 6.8 ± 1.4 days (p < 0.001), skin dryness - of 9.8 ± 1.1 and 12.3 ± 1.6 days, respectively (р < 0.001).Conclusion: Adding enterosorbent containing pectin, inulin and fennel extract to the basic therapy of moderate AD makes it easier to arrest the clinical manifestations of an acute allergic process.